Quantitative component of population development dynamics - Savchuk, Aleksey A. (Journal of the Belarusian State University. Philosophy and Psychology, 2026)
This article examines the quantitative component of population development dynamics, coupled with the analysis of natural and mechanical population movement indicators. In order to determine the specifics of the demographic situation in Belarus, the aging rate and population density are also considered.
Keywords: demographic situation; demography; birth rate; population development dynamics; statistical analysis